RELEASING DEPENDENCE SUBSIDY FOR FUEL OIL THROUGH CONVERSION PROGRAM OF GAS FUEL ON A VEHICLE TOWARD THE NATIONAL ENERGY SECURITY - Susanti, Vita; Hartanto, Agus; Subekti, Ridwan Arief (Journal of S&T Policy and R&D Management, 2013)
Based on BPS data in 2010, the number of motor vehicles in Indonesia as many as 76.9 million units, the number of vehicles on the island of Java alone approximately 44.4 million units. More than 57% of the number of motor vehicles in Indonesia on the island of Java. This is the background to the potential conversion of fuel oil to CNG fuel for vehicles on the island of Java. In addition, the end of 2014 the gas pipeline Trans Java linking West Java to Central Java and Central Java to East Java will operate. These two components, namely the large number of vehicles and the operation of the gas pipeline Trans Java offer more value than if the conversion program implemented in other islands. Studies have been done on the conversion of fuel oil to CNG fuel vehicles, especially in the area around the gas pipeline Trans Java. This paper will map potential locations for the implementation of the conversion program, conversion targets in each region, the need of CNG, Gas Stations number, size reduction of subsidies, and profits for NGV users. Formulation of strategies are required in migrating to CNG, the mapping problem in doing the conversion, and prepare for technology transfer. Vehicles that will be converted are gasoline-fueled vehicles, consists of public transportation, private and services. For public transport and services. Conversion is done 100%. Non public transportation (vehicles) converted only by 10%. The conversion vehicles will be done for 3 years gradually. Target conversion for 3 years at 1.1 million units NGV. The amount of the required gas allocation as many as 10.7 million klsp, which is needed as many as 2,857 SPBG. Saving from subsidy about 35.44 trillion rupiahs. To make the program successful requires the government policy and good coordination between relevant agencies in particular to overcome obstacles, problems, and to prepare for the transfer of technology.